Engineered models for studying blood-brain-barrier-associated brain physiology and pathology - Kim, Hong Nam (The Organoid Society, 2021)
The blood-brain barrier (BBB) is a transport barrier that suppresses the translocation of potentially harmful substances to the brain tissue. Although the BBB is known to be associated with many kinds of neuropathology, such as neuroinflammation and neurodegenerative diseases, the conventionally used animal and Transwell models cannot provide sufficient information due to genetic and functional heterogeneity in comparison with humans and limited monitoring capabilities. Recently, human cell-based three-dimensional BBB models have been developed, and these models provide in vivo-like BBB structures and functions. In this review, we provide an overview of the recent advances in BBB models with a particular focus on the simulation of BBB-associated brain physiology and neuropathology. To this end, important factors for recapitulating the in vivo characteristics of the BBB are described. Furthermore, approaches to recapitulate the BBB physiology using engineering methods are summarized. The applications of BBB models in the study of neuropathology, such as inflammation and neurodegenerative diseases, are also presented.